A vingança do áudio - Paiva, Ana Sofia (2020)
O som tridimensional, nomeadamente o som binaural, não é uma tecnologia recente. Desde os finais do século XVIII que as primeiras experiências deram aso às contínuas tentativas para percecionar o som tal como o ser humano o escuta. As mais recentes inovações, nomeadamente no século XX, permitiram a melhoria deste tipo de tecnologia e a possibilidade de a aplicar às mais diversas indústrias, como o cinema ou os videojogos. A rádio não escapou a esta tendência e o som binaural é utilizado tanto no entretenimento como no jornalismo. Neste artigo, pretendemos destacar o papel do áudio e contrariar a premissa de que o “vídeo matou a estrela da rádio”. Começamos assim por abordar o conceito de som binaural para depois nos concentrarmos na análise das utilizações que têm sido feitas desta tecnologia no campo do jornalismo e do entretenimento radiofónico, sublinhando a forma como assistimos à revitalização da importância do áudio. Three-dimensional sound, namely binaural sound, is not a recent technology. Since the end of the 18th century, the first experiences gave rise to the continuous attempts to perceive sound as the human being listens to it. The most recent innovations, namely in the 20th century, allowed the improvement of this type of technology and the possibility of applying it to the most diverse industries, such as cinema or video games. Radio has not escaped this trend and binaural sound is used in both entertainment and journalism. In this article, we aim to highlight the role of audio and counter the premise that “video killed the radio star”. We started by approaching the concept of binaural sound through a survey of academic works that, in recent years, have recovered this concept in order to establish a connection with the radio, podcasts and / or new radio narratives. In a second step, we focus on mapping some of the works that have been carried out in the field of radio, both nationally and internationally, and that have resorted to this technology, whether they are journalistic or entertainment. Through this intersection, between academic research and content production, we seek to highlight the way in which we have been witnessing a revitalization of the importance of audio and the awakening of new sound experiences.